Analysis of Coral Condition at Kecinan Beach, North Lombok - Hilman Ahayadi; Derksen, Engelina Noer Soraya; Candri, Dining Aidil; Virgota, Arben; Setyaningrum, Tri Wahyu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The high level of construction and community activities at Kecinan Beach can affect the condition of the coral reef ecosystem. The health condition of the coral reef ecosystem can be assessed by the percentage of live coral cover within the ecosystem. North Lombok is one of the regencies on the island of Lombok that has experienced coral reef ecosystem damage, with this regency having the lowest percentage of live coral cover compared to other regencies. This study aims to determine the diversity of coral reef lifeform types and assess the health status of coral reefs at Kecinan Beach, North Lombok Regency. Data on coral reef lifeform types were observed using Coral Finder 2.0 Indo Pacific. Data collection was conducted using the UPT (Underwater Photo Transect) method at two different depths: 1-5 meters and 6-10 meters. The research results indicate that the coral reef ecosystem at Kecinan Beach is in poor condition. The percentage of live coral cover at depths of 1-5 meters is 3,58%, and at depths of 6-10 meters is 0,90%. There is ten types of coral reef lifeforms were found distributed across both depths: Acropora branching, Acropora tabulate, coral branching, encrusting, foliose, heliopora, massive, millepora, mushroom, and submissive. Diversity, evenness, and dominance indexs shows even distribution of lifeforms with no dominant species in the coral reef ecosystem at Kecinan Beach, North Lombok.